1989
DOI: 10.1161/01.hyp.13.6.878
|View full text |Cite
|
Sign up to set email alerts
|

Baroreceptor sensitivity in prehypertensive young adults.

Abstract: Decreased baroreceptor reflex sensitivity has been implicated in the pathogenesis of hypertension. The purpose of this study is to determine if alterations of baroreceptor function precede the development of hypertension in humans. Baroreceptor function was evaluated in 13 young adult white men with relatively high blood pressures sustained for 12 to 15 years and 12 age-matched men with sustained relatively low blood pressures. High pressure baroreceptor activity was evaluated by measuring change in pulse inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
1

Year Published

1990
1990
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
1
4
1
Order By: Relevance
“…7 Kotchen and colleagues reported significantly greater supine and seated diastolic blood pressure in 12 normotensive men during a low (10 mEq/day) ν a high (250/mEq/day) sodium diet. 20 Another report confirms the observation of higher seated diastolic blood pressure during a low ν high salt diet and extends these observa tions to both black and white hypertensive and normo tensive subjects. 21 Therefore, data from our study and from the other investigations cited suggest that the blood pressure re sponse to dietary NaCl restriction is not uniformly a depressor response.…”
Section: Effects Of Dietary Nacl Restriction On Mean Arterial Pressur...supporting
confidence: 56%
“…7 Kotchen and colleagues reported significantly greater supine and seated diastolic blood pressure in 12 normotensive men during a low (10 mEq/day) ν a high (250/mEq/day) sodium diet. 20 Another report confirms the observation of higher seated diastolic blood pressure during a low ν high salt diet and extends these observa tions to both black and white hypertensive and normo tensive subjects. 21 Therefore, data from our study and from the other investigations cited suggest that the blood pressure re sponse to dietary NaCl restriction is not uniformly a depressor response.…”
Section: Effects Of Dietary Nacl Restriction On Mean Arterial Pressur...supporting
confidence: 56%
“…Our results, however, contrast with the findings of Kotchen et al. () who reported no differences in cardiovagal BRS in a cohort of 13 Caucasian males with prehypertension compared to 12 matched normotensive controls. This difference might be due in part to the fact that Kotchen et al.…”
Section: Discussioncontrasting
confidence: 99%
“…Experimental studies (Gordon and Mark ) have reported impaired baroreceptor discharge in prehypertensive Dahl salt‐sensitive rats compared to normotensive rats (Gordon and Mark ), while human studies have shown mixed results (Kotchen et al. ; Rea and Hamdan ; Pal et al. ), likely due in part to differences in technique and study populations including racial differences.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, 44% of the men were salt sensitive but 41% were reverse responders, who had higher blood pressure on the low-salt diet. The authors went on to note, '… a study of hypertensive patients by Longworth et 32 Another report confirms the observation of higher seated diastolic blood pressure during a low v high-salt diet and extends these observations to both black and white hypertensive and normotensive [participants] 33 '. 22 All of these studies indicate that a large percentage of the population does not have a clinically meaningful drop in blood pressure with salt restriction and that in many cases there can even be an increase in blood pressure.…”
Section: Studymentioning
confidence: 84%